Demografischer Wandel und Verkehr: Wirkungen und Konsequenzen. - Topp, Hartmut H. (Deutscher Verkehrs-Verl., 2006)
Weltweit wächst die Bevölkerung weiter; in großen Teilen Europas aber stagniert sie und wird ab 2015 bei stark zunehmender Alterung schrumpfen. In Deutschland begann die Schrumpfung zunächst in Ostdeutschland kurz nach der Wiedervereinigung: 1989 lebten in Ostdeutschland 16,6 Mio. Menschen, 2003 waren es noch 15 Mio., ein Verlust von 10 % in 14 Jahren. Das lag an der Überlagerung der extrem niedrigen Geburtenrate (0,8 Kinder pro Frau) mit der starken Binnenwanderung in die westlichen Bundesländer in der Umbruch- und Übergangssituation der 1990er Jahre. difu

Demographic changes' impact and consequences in relation to traffic planning. Demographic changes tend to affect the level and location of an increasingly ageing population. The expansion and downsizing of townships and regions appears to run in parallel. Contractions have varying effects on traffic composed of pedestrians, bicycles, cars and the local public transport: distances grow longer / road capacity problems diminish / local public transport services are reduced. The element of competition tends to shift towards the car. The hitherto regular clientele of the local public transport will evetually consist of travellers who can choose their modes of transport freely and appreciate better quality of service. Long term problems of the local public transport will reach beyond the operators' current restructuring process. Evolution from the inside, not from the outside, appears to be the main strategy target with regard to decreasing townships. difu
Keywords: Verkehr; Mobilität; Dienstleistung; Verkehrsplanung; Verkehrsstatistik; Bevölkerungsentwicklung; Verkehrsnachfrage; ÖPNV; Prognose; Bevölkerungsstatistik; Stadtverkehr; Schrumpfung; Demographischer Wandel; Verkehrsleistung